Prediction of particle charging in a dilute pneumatic conveying system. Issue 7 (27th February 2013) - Bunchatheeravate, Poom; Curtis, Jennifer; Fujii, Yusuke; Matsusaka, Shuji
<x xml:space="preserve">Abstract</x> When particles are transported in pipelines, they acquire electrostatic charges as they come into contact with the pipe wall. Charged particles can cause problems such as particle agglomeration, blockage, and explosion. Understanding the particle charge can help to prevent these issues. This study investigates a technique for predicting the particle charge in a straight pipe of any given length, as well as the pipe length at which electrostatic equilibrium occurs, through experimentation in a short 1‐m pipe section. Experimentation with five different types of particles and four pipe wall materials at longer pipe lengths were used to validate the technique. This predictive technique is applicable to a range of particle shapes and sizes under the restriction that charge transfer is due to impact charging. © 2013 American Institute of Chemical Engineers AIChE J, 59: 2308–2316, 2013